Principal Directions of Evaluation of Expert Evidence - A. A. Kuznetsov (Сибирское юридическое обозрение, 2015)
The article deals with the evaluation procedure of expert evidence, which was prepared subsequent to the results of the examination of evidence. Expert evidence is evaluated from the point of view of relevance of evidence, its admissibility and credibility. The author recommends the response sequence of an investigator while evaluating expert evidence.